Sistem Multi-Sensor Nirkabel Berbasis RFID Untuk Pemantauan Keaktifan Siswa - Zakiah Zakiah; Yuwaldi Away; Fitri Arnia; Andri Novandri (Universitas Syiah Kuala, 2019)
This study aims to design a multisensor observation system, develop a microcontroller-based prototype with ESP8266 and RFID modules, and analyze the performance of the prototype. From the testing carried out by tagging each time students do activities, the client tag data will be sent to the server, and the results are displayed PLX-DAQ. With the 50 tag cards that have registered the IDs of each student, it shows that those who attend the schedule will be given the logic